Sistem Pendukung Keputusan Kelayakan Panen pada Tanaman Jagung - Siprianus Septian Manek; Umbu Joka (Fakultas Pertanian, Universitas Timor, 2020)
Corn is one of the most important carbohydrate-producing food crops in the world. For some of the world's population, including in Indonesia, corn is used as a staple food. Corn can be harvested if the physiological ripe conditions are 80-90 days, the husk of the husks is brown, the hair of the corn on the cob is dry and black, the population for dry husks reaches 90%, the texture of the corn kernels is quite hard, and there are black dots on the tip of the corn kernels. Some farmers, especially those who are just starting to learn to plant corn or who do not have sufficient knowledge in agriculture, harvest corn earlier or later than the harvest time. This will have an impact on the chemical composition of the corn which will determine its quality. Therefore, a computer-based system model is needed that can provide convenience in analyzing data, calculating the assessment of harvest-worthy criteria, and helping to process data into information for making decisions. A decision support system (DSS) is the right choice for the above problem. The SPK is designed using the Simple Additive Weighting (SAW) method, which is one of the Fuzzy Multiple Attribute Decission Making (FMADM) methods. The SAW method was chosen because the weighted criteria calculation is not too complicated, so it is easy to learn. The system built is expected to help farmers accelerate the process of selecting criteria and reduce errors in determining the feasibility of harvesting the corn plant